Observer-Rated Alexithymia and its Relationship with the Five-Factor-Model of Personality. Issue 2 (26th May 2016) - Rosenberg, Nicole; Rufer, Michael; Lichev, Vladimir; Ihme, Klas; Grabe, Hans-Jörgen; Kugel, Harald; Kersting, Anette; Suslow, Thomas
Studies examining the relationship between alexithymia and personality exclusively employed self-report measures of alexithymia. In the present study, we examined the relationship of both observer-rated and self-reported alexithymia with the Big Five personality dimensions. We administered the Toronto Structured Interview for Alexithymia (TSIA) as an interview-based measure of alexithymia and, in addition, two self-report questionnaires, the 20-item Toronto Alexithymia Scale (TAS-20) and the Bermond-Vorst Alexithymia Questionnaire (BVAQ). Fifty-one university students were interviewed and completed the alexithymia scales and the NEO Five-Factor Inventory. In contrast to TAS-20 and BVAQ, the Difficulty identifying feelings (DIF) scale of the TSIA was found to be unrelated to neuroticism, suggesting that the frequently reported association between DIF and neuroticism could be due to the use of self-report scales. In contrast, the affective dimension of alexithymia, measured by the BVAQ, was even negatively related with neuroticism. Thus, a paucity of fantasy and little emotional arousal goes together with increased emotional stability. Furthermore, we revealed negative correlations between interview-based alexithymia scores and openness to experience and agreeableness, which cross-validated the self-report findings. Finally, extraversion and conscientiousness each showed only one negative correlation, namely with subscales of the BVAQ. Taken together, our findings show that on the basis of interviews there is no evidence for a relation of DIF with neuroticism, while associations of alexithymia with low openness to experience and low agreeableness emerged irrespective of assessment approach. The relations of alexithymia with personality are discussed in the light of different measurement approaches.